THE MORAL AND CULTURAL ROLE OF EUPHEMISM IN SOCIETY - Atadjanova, Sevara (Журнал иностранных языков и лингвистики, 2023)
Our article covers the concept of euphemism as a means of language, as well as examples of this phenomenon in English and Uzbek. In the development of society over the years, the socialist changes taking place in our society are directly and indirectly related. These changes are aimed at the maturation of humanity and serve as beacons of humanity calling upward.